2011
DOI: 10.1007/s13204-011-0037-9
|View full text |Cite
|
Sign up to set email alerts
|

Gold on oxide-doped alumina supports as catalysts for CO oxidation

Abstract: The effect of doping a commercial alumina support with metal oxides of Ce, Co, Cu, Fe, La, Mg, Mn, Ni and Zn was investigated. Doped d-Al 2 O 3 samples were obtained by simple physical mixture (PM) of the alumina with the desired commercial oxide and by traditional impregnation of alumina with precursor salts of the same metals followed by calcination (IC). The metal load (7% wt.) was the same in both cases. Gold (1% wt.) was loaded using a liquid phase reductive deposition method. The obtained materials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 88 publications
3
10
0
Order By: Relevance
“…Generally, the gold catalysts on CeO2/Al2O3 and Y-doped CeO2/Al2O3 supports prepared by MM exhibited better PROX behaviour as compared to the corresponding supports prepared by IM. These results are in agreement with the study of Carabineiro et al [13] showing that gold catalysts on supports obtained by simple physical mixture of commercial alumina and different metal oxides (including CeO2) were much more active in CO oxidation than the gold catalysts on corresponding supports prepared by traditional way of impregnation. The positive effect of yttrium [9] was confirmed by the higher activity of AuY20CeAlIM then that of Au20CeAlIM catalyst.…”
Section: Catalytic Measurementssupporting
confidence: 93%
“…Generally, the gold catalysts on CeO2/Al2O3 and Y-doped CeO2/Al2O3 supports prepared by MM exhibited better PROX behaviour as compared to the corresponding supports prepared by IM. These results are in agreement with the study of Carabineiro et al [13] showing that gold catalysts on supports obtained by simple physical mixture of commercial alumina and different metal oxides (including CeO2) were much more active in CO oxidation than the gold catalysts on corresponding supports prepared by traditional way of impregnation. The positive effect of yttrium [9] was confirmed by the higher activity of AuY20CeAlIM then that of Au20CeAlIM catalyst.…”
Section: Catalytic Measurementssupporting
confidence: 93%
“…These authors used this method to prepare Au/TiO 2 materials, and state that it represents an environmentally and economically favorable route to the production of highly active gold catalysts. This method has been used with great success for other supports, such as metal oxides and carbon materials by Carabineiro et al (2010a,b,c,e,f, 2011a,b, 2012a,b, 2013, 2016); Bastos et al (2012); Rodrigues et al (2012b); Silva C. G. et al (2014); Soria et al (2014); Pérez et al (2016). One example is shown in Figure 1b, where much smaller and better dispersed gold nanoparticles are seen on ceria.…”
Section: Gold Catalyst Preparation Methodsmentioning
confidence: 99%
“…It has been conventionally described as a defect spinel (Fd-3m) with the idealized formula Al 21+1/3ᮀ2+2/3 O 32 , where ᮀ denotes a vacancy [21]. Many studies have been reported on oxide-doped alumina supported AuNPs [4,19,[22][23][24][25]. It was reported that lithium oxide (Li 2 O) has a promoting effect on the activity of the Au/␥-Al 2 O 3 catalyst in CO oxidation [4,25].…”
Section: Introductionmentioning
confidence: 99%